An Analysis of the Challenges Faced by Female UndergraduateEFL Students in Speaking English at ULM (Journal of Asian Development Studies, 2024)
Speaking skills play an important role in daily life conversation through which we express feelings, emotions, and ideas easily and confidently. English has gained the status of a global language as it is spoken and understood all around the world. English is the medium of communication enabling people of different linguistic backgrounds to connect, cooperate, and collaborate. The present study investigates the challenges that undergraduate female EFL students face in speaking English. The present study is an attempt to find out the reason for the challenges faced by undergraduate female students in speaking English at ULM and how we defeat these challenges through some achievable actions. To find out the challenges that undergraduate female students in speaking English at ULM, we used the quantitative method. We collect data through questionnaires from the different semester students of the department of English and Applied Linguistics, and then we analyze it on SPSS software by applying the descriptive statistical analysis method. The finding reveals various factors or challenges including social, environmental, economic, and psychological. Moreover, the study also highlights some possible strategies to approach these challenges and enrich English speaking fluency among female EFL students. Understanding and confronting these challenges is critical for developing English language education for female undergraduate EFL students, thus upgrading their academic and professional avenues.